2019
DOI: 10.1039/c9sc01563a
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Baeyer–Villiger oxidation: classical and parallel kinetic resolution of 3-substituted cyclohexanones and desymmetrization of meso-disubstituted cycloketones

Abstract: Classical kinetic resolution, parallel kinetic resolution and desymmetrization were achieved by asymmetric BV oxidation of 3-substituted and meso-disubstituted cycloketones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Most recently, Feng's group reported that their N , N′ ‐dioxide‐Sc(III) complex‐catalyzed B‐V oxidation could be extended to the more challenging kinetic resolution of racemic 3‐substituted cyclohexanones by fine turning the structure of the chiral N , N′ ‐dioxide ligand . When using 28 as the chiral ligand, together with 0.5 equiv.…”
Section: Kinetic Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, Feng's group reported that their N , N′ ‐dioxide‐Sc(III) complex‐catalyzed B‐V oxidation could be extended to the more challenging kinetic resolution of racemic 3‐substituted cyclohexanones by fine turning the structure of the chiral N , N′ ‐dioxide ligand . When using 28 as the chiral ligand, together with 0.5 equiv.…”
Section: Kinetic Resolutionmentioning
confidence: 99%
“…This catalytic system is also effective in the asymmetric B‐V oxidation of meso cyclic ketones (Scheme ) . In the presence of chiral N , N′ ‐dioxide 62 ‐derived Sc(III) complex (10 mol%), a series of cis ‐3,5‐diarylcyclohexanones could be oxidized to afford products 61 in excellent yields and ee values.…”
Section: Desymmetrizationmentioning
confidence: 99%
“…To the best of our knowledge, only one example, i.e. , 2-phenylcyclobutanone, was reported by Feng and co-workers in 2014, 5 w and a moderate ee value and poor rs ratio were observed using their own developed privileged chiral N , N ′- dioxide/Sc( iii ) system that exhibited excellent activities and enantioselectivities for a wide range of cyclohexanones and cyclopentanones in the desymmetric or kinetic resolution of B–V oxidations 5 v – y and other diverse asymmetric transformations. 6 From a synthetic perspective, there are some synthetic challenges in the classical kinetic resolution of 2-substituted cyclobutanones and their derivatives, including the following: (1) easy racemization of the unreacted 2-substituted enantiomer is inevitable due to the effect of the adjacent carbonyl group during its purification at room temperature; (2) both the regioselectivity and enantioselectivity of the reacted enantiomer can be simultaneously controlled in the subsequent transformation of its key Criegee intermediates; 7 (3) the chiral catalyst could tolerate the corresponding oxidation conditions; and (4) the lack of appropriate functional groups in 2-substituted cyclobutanones which could interact with the chiral catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Baeyer–Villiger (B–V) oxidation, which was first reported in 1898, 1 is an important transformation in organic synthesis because it provides a concise and convenient approach toward esters from ketones or aldehydes, especially lactones from cycloketones. 2–5 Asymmetric B–V oxidation using chiral substrates as the starting materials has been widely applied to prepare chiral lactones; however, its catalytic asymmetric version was explored by Bolm in the 1990s. 5 a Since then, catalytic asymmetric B–V oxidation has received much attention from synthetic chemists, and chiral bio-, 3 org-, 4 and metal catalytic systems 5 have been developed, delivering valuable synthetic building blocks such as γ-, δ-, and ε-lactones with excellent enantioselectivities and/or regioselectivities (rs).…”
Section: Introductionmentioning
confidence: 99%
“…3 Thousands of studies are devoted to this reaction [4][5][6][7][8] and its regio-and stereoselective versions were developed. [9][10][11][12] An important monomer for polyesters and polyamidescaprolactone is produced via BV reaction in industry. 13,14 Throughout its history, several mechanisms were suggested for the BV oxidation.…”
Section: Introductionmentioning
confidence: 99%